SOCIAL CAPITAL IN POVERTY ALLEVIATION THROUGH PRO-POOR TOURISM CONCEPT IN SLUM AREA (CASE STUDY: KELURAHAN JODIPAN, MALANG CITY) (GEOMATE Journal, 2019)
Kelurahan Jodipan is one of the slums in Malang City which is at downtown and river bank of Brantas. In 2014, Kelurahan Jodipan became the center of world's attention because it can change the image of its area, be a colorful residential area that became one of the must-visit tourist destinations in Malang. The concept of tourism can indicate as the application of Pro-Poor Tourism concept. Tourism in Kelurahan Jodipan requires contribution and participation of the community to continue the tourism activities. Therefore, this study aims to assess the level of social capital in alleviating poverty through Pro-Poor Tourism concepts in slums. The analytical method used in this research is the Rate of Participation (RoP) analysis and Structural Equation Modeling analysis using MPLUS to know the relationship between variables and dominant factors that influence. The result of RoP analysis is the level of community participation of RW.02 Kelurahan Jodipan belongs to the low participation class. The average community follows one institutional in Kelurahan Jodipan. The results of SEM analysis is the association between social capital and tourism proportional. That is, the better the social capital in the community, the better the management of the environmental tourism.  Second, the relationship between social capital and tourism with community poverty is inversely proportional. That is, the higher the social capital and the better the tourism activity then the poverty in the region will be smaller. The last result is Pro-Poor Tourism tourism activities, in this case, can reduce the poverty level of the community.